A multivariate model of the offence behaviours of South African serial killers - Hodgskiss, Brin Allan (Rhodes University, Faculty of Humanities, Department of Psychology)
It was hypothesised that there would be behavioural consistencies in the offences of South African serial killers. The themes underlying these observable differences can help us understand the nature of these offences. Crime scene data was ohtained from police records, and structured, in-depth offender interviews. 73 offences, committed by 13 offenders, were analysed. The analysis used Smallest Space Analysis (SSA), a Multidimensional scaling (MDS) procedure. This analysis revealed systematic patterns of behaviour in the offences. It was found that the focus of these offences is an impersonal, hostile, and act-focused murder were the victim is treated as a depersonalised object. Empirical support for an underlying thematic structure to these offences was also provided. The offence themes identified relate to the nature of the actions committed during the offence, and the function these actions had for the offender. These fmdings thus support the hypothesis that these offences will display meaningful behavioural variation. These findings have direct utility in the investigation and study of serial killing in South Aflica. They also provide the basis for comparison with previously suggested typologies of serial killing, and indicate directions for future research into this phenomenon in the South African setting.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Serial murderers -- South Africa -- Psychology; Criminal behavior